Survivorship During Starvation for Cimex lectularius L. - Carlyle C. Brewster; Dini M. Miller; Andrea M. Polanco (Insects, 2011)
Four bed bug strains (Cimex lectularius) with different levels of pyrethroid resistance were evaluated to determine their ability to survive extended periods of starvation. First instar bed bugs of all strains were the most vulnerable to starvation (13.8–36.3 days mean survival time). Fifth instars and adults survived the longest during starvation (41.5–142.6 days). Significant differences in survivorship during starvation were observed between resistant and susceptible strains of bed bugs. Overall, all immature and adult stages of the resistant bed bug strains had significantly shorter survival times than those of the susceptible strains (P < 0.05).